Implementasi Program Pendaftaran Tanah Sistematis Lengkap di Kelurahan Wangurer Utara Kecamatan Madidir Kota Bitung - Jeane Mantiri; Devie Siwij (Institut Pemerintahan Dalam Negeri, 2023)
This study aims to determine the implementation of the Complete Systematic Land Registration Program in North Wangurer Village, Madidir District, Bitung City. Using a qualitative descriptive approach, with data collection techniques taken through observation, interviews, and documentation. Data sources include primary and secondary data sources. Primary data sources were obtained from informants, namely: the North Wangurer sub-district government and the community. Meanwhile, secondary data sources include related documents. Technical analysis of data is taken through components: data reduction, data presentation and drawing conclusions. The results showed that many people were unable to meet the requirements needed in managing the registration of the Complete Systematic Land Registration Program. Lack of clear information, minimal understanding and knowledge of the community about the objectives and benefits of the program, as well as the absence of complete document data, both physical data and juridical data, among others, become obstacles for the community, so they are reluctant to manage/follow the PTSL program.